DERIVATION AND AFFIXATION PROCESS IN SPEECH OF DANANJAYA HETTIARACHCHI - Susilawati Susilawati; Fennia Bintari Putri (IKIP Siliwangi, 2018)
This journal discussed about the derivation and affixation process in English speech. Derivation is one type of linguistics morphology that involved word formation, and there are affixes used to construct new word. The aims is to analyzed what kinds of derivation and affixation mostly used on Dananjaya Hettiarachchi speech (I See Something). The data are all words containing derivation and affixation that found in Dananjaya Hettiarachchi Speech entitled I See Something. The descriptive qualitative method used to analyze the data. The technique of data collecting is documentation from https://www.linkedin.com/ accessed on May 23, 2018. From the data collection, the researchers found that adjective formation is the mostly used in the derivational process, which consist of 6 variations in 13 words. The second is noun formation, which consist of 3 variations in 12 words. The third is adverb formation, which consist of 3 variations in 3 words. And the last is verb formation, which consist of 2 variations in 2 words. While the affixes that mostly used is suffix, which consist of 11 suffixes used. The second is prefixing only 1 prefix used. And the researchers didn’t found infix on the speech text. Keywords: Derivation, Affixation, Process, Speech.